6x+3x=2x+3

Simple and best practice solution for 6x+3x=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+3x=2x+3 equation:



6x+3x=2x+3
We move all terms to the left:
6x+3x-(2x+3)=0
We add all the numbers together, and all the variables
9x-(2x+3)=0
We get rid of parentheses
9x-2x-3=0
We add all the numbers together, and all the variables
7x-3=0
We move all terms containing x to the left, all other terms to the right
7x=3
x=3/7
x=3/7

See similar equations:

| b4=16= | | 17-9x=189 | | C^2+27c=-5 | | m+-9.59=-5.59 | | 80w=480 | | n=5(n+3)=38 | | 15s=-840 | | 4(v-5)=-7v | | 25=7x+4-4 | | 11w+17w=-20 | | b+5/3=7 | | X-11y=96 | | -2(2z+1)=6 | | -16w=-752 | | 286=-13n | | 3(3n+5)=87 | | -5x-5(x+1)=-3(3x+5) | | 3x-8=5+6x | | 13(y-3)=3(4y+2)-45 | | M=(4x+9) | | m+227=284 | | 3(x-4)=2(x+1)-5 | | 10x-25x-8=7x-12 | | 15=q/18 | | -5u+6=31 | | 7.2-y=8 | | q+-93=-53 | | C(x)=16,662; | | 3(−5x+4)+5x−1=−39 | | -17x=4x-18 | | 4x-10=2+7x | | 3.5x-4=-4 |

Equations solver categories